NKG2D Ligand Shedding in Response to Stress: Role of ADAM10 - Zingoni, Alessandra; Vulpis, Elisabetta; Loconte, Luisa; Santoni, Angela (Frontiers in Immunology, 2020)
NKG2D is an activating receptor expressed by NK cells and some subsets of T cells and represents a major recognition receptor for detection and elimination of cancer cells. The ligands of NKG2D are stress-induced self-proteins that can be secreted as soluble molecules by protease-mediated cleavage. The release of NKG2D ligands in the extracellular milieu is considered a mode to finely control their surface expression levels and represents a relevant immune evasion mechanism employed by cancer cells to elude NKG2D-mediated immune surveillance. A disintegrin and metalloproteinase 10 (ADAM10), a catalytically active member of the ADAM family of proteases, is involved in the cleavage of some NKG2D ligands in various types of cancer cells either in steady state conditions and in response to an ample variety of stress stimuli. Appealing immunotherapeutic strategies devoted to promote NK cell-mediated recognition and elimination of cancer cells are based on the upregulation of NK cell activating ligands. In particular, activation of DNA damage response (DDR) and the induction of cellular senescence by chemotherapeutic agents are associated with increased expression of NKG2D ligands on cancer cell surface. Herein, we will review advances on the protease-mediated cleavage of NKG2D ligands in response to chemotherapy-induced stress focusing on: i) the role played by ADAM10 in this process; ii) the implications of NKG2D ligand shedding in the course of cancer therapy and in senescent cells.